الأثر التربوي للإعلام الفضائي في سلوك الأفراد - القطاونة، نهى صبري محمد; حسين، أحمد ضياء الدين (جامعة العلوم الإسلامية العالمية - عمادة البحث العلمي, 2020)
يهدف هذا البحث إلى بيان الأثر التربوي للإعلام الفضائي في سلوك الأفراد، من خلال بيان مفهوم الإعلام الفضائي ونشأته وتطور استخدامه، وكذلك بيان إيجابيات وسلبيات الإعلام الفضائي في القيم السلوكية للأفراد، ودور المؤسسات التربوية والإعلامية في كيفية التعامل مع الإعلام الفضائي، وخلص البحث إلى أن التلفاز سلاح ذو حدين، ولذا يجب الحرص في التعامل معه، وأن للمؤسسات التربوية والإعلامية دورا كبيرا في بيان كيفية التعامل مع الإعلام الفضائي للحد من آثاره السلبية في سلوك الأفراد وانعكـاس ذلك على المجتمع.
This study aims to explore the educational effect of space media on the behavior of individuals by presenting the concept, evolution and development of space media in the era of globalization. It also presents the advantages and disadvantages of space media in behavioral values of individuals, and the role of educational institutions and media in dealing with space media. The study concluded that television is a double-edged sword; therefore, people should be cautious when using it. The study indicated that educational and media institutions play a significant role in explaining how to deal with space media in order to reduce the negative effects on the behavior of the individual and society.
Keywords: وسائل الإعلام -- الإعلام الفضائي -- القنوات الفضائية -- القيم السلوكية